Ispol'zovanie techniceskoj podgotovki futbolistov v povyšenii ball'noj ocenki za komponenty programmy figuristov etapa sportivnoj specializacii - Cherepanova, I. O.; Dunaev, K. S.; Seyranov, S. G.; Fomin, Yu. A. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
This article discusses the components included in the second assessment for the skater`s rental program, and ways to increase the score for their performance by the means and methods used by football players in technical training, which are based on the development of "ice feeling", improvement of motor orientation and proprioceptive sensitivity of skaters 9- 10 years of sports specialization. The use of technical training of football players in the training process of figure skaters as a means of increasing the coordination component, speed qualities, speed, step frequency when performing a variety of paths of steps and ligaments between the elements, as a result of the pedagogical experiment proved to be an effective means, as evidenced by the testing at the end of the experiment.